Drosophila melanogaster: a model organism for controlling Dipteran vectors and pests. (June 2015) - Zolfaghari Emameh, Reza; Syrjänen, Leo; Barker, Harlan; Supuran, Claudiu T.; Parkkila, Seppo
Abstract Beta-carbonic anhydrases (β-CAs) have been recently reported to be present in many protozoan and metazoan species, whereas it is absent in mammals. In this review, we introduce β-CA from Drosophila melanogaster as a model enzyme for pesticide development. These enzymes can be targeted with various enzyme inhibitors, which can have deleterious effects on pathogenic and other harmful organisms. Therefore, β-CAs represent a new potential target to fight against Dipteran vectors and pests relevant to medicine, veterinary medicine, and agriculture.